The Diagnostic Value of Irisin in Pediatric Patients with Acute Abdominal Pain - Fatma Sarac; Sevgi Buyukbese Sarsu; Selman Yeniocak; Kamil Sahin; Esma Yucetas; Dogan Yildirim; Macit Koldas; Ozlem Uzun (Emergency Medicine International)
Objectives. Diagnosis of pediatric patients presenting to the Emergency Department with acute abdominal pain is not always easy. The purpose of this study was to investigate the effectiveness of irisin, a peptide hormone with reactivity shown in the appendix and neutrophils, in the differential diagnosis of pediatric patients with acute abdominal pain. Methods. 162 subjects consenting to participate, including 112 patients presenting to the Pediatric Emergency and Pediatric Surgery clinics with acute abdominal pain and 50 controls, were enrolled in the study. Blood was collected from all patients following initial examination for irisin, WBC, and CRP investigation. Results. Mean irisin levels in cases of acute appendicitis (AA) and perforated appendicitis (PA) were statistically significantly higher compared to nonspecific abdominal pains and the control group. No statistically significant difference was observed in irisin levels between AA and PA cases. WBC and CRP levels were also significantly higher in cases of AA and PA compared to nonspecific abdominal pains. Conclusions. Differential diagnosis of acute abdominal pains in children and deciding on surgery are a difficult and complex process. Our study shows that irisin can be a useful biomarker in differentiating AA and PA from other acute abdominal pains in children.